Analisis Peran Guru Pendidikan Agama Islam untuk Membentuk Kesadaran Sosial Siswa : Studi Kasus di SMP YPP SOBANG - Rohmatullah; Mumu Zainal Muttaqin; Hani Muflihah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The study entitled “Analysis of the Role of Islamic Religious Education Teachers in Developing Students’ Social Awareness (A Case Study at YPP Sobang Junior High School)” was motivated by the importance of Islamic Religious Education (Pendidikan Agama Islam / PAI) teachers in fostering students’ social awareness, which does not emerge automatically but must be cultivated through education. This study was based on conditions at YPP Sobang Junior High School, where students still demonstrated low environmental awareness, limited participation in social activities, and suboptimal internalization of religious values. The research questions focused on the role of PAI teachers in developing students’ social awareness, the strategies they employ, and the impact of PAI learning on students’ social attitudes. The objective of this study was to identify the roles, strategies, and impacts of PAI teachers in fostering students’ social awareness. This research employed a descriptive qualitative method with a case study approach. Data were collected through observations, interviews, and documentation involving PAI teachers, the principal, curriculum staff, and students. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that PAI teachers play a significant role in developing students’ social awareness through religious habituation, role modeling, and social activities. The strategies implemented included contextual learning, mutual assistance, and cooperation. The impacts were reflected in increased empathy, social concern, responsibility, and social interaction among students, although challenges remained in terms of student participation and the influence of the external environment outside the school.